2013 Conference on Lasers &Amp; Electro-Optics Europe &Amp; International Quantum Electronics Conference CLEO EUROPE/IQEC 2013
DOI: 10.1109/cleoe-iqec.2013.6801054
|View full text |Cite
|
Sign up to set email alerts
|

Compact gigawatt-class sub-picosecond Yb:YAG thin-disk regenerative chirped-pulse amplifier with high average power at up to 800 kHz

Abstract: Ultrashort pulses are capable of processing practically any material with a negligible heat affected zone [1]. For productive industrial applications a pulse duration of about 5 ps is a well established compromise between being faster than the electron-phonon interaction time of the material and being long enough to suppress detrimental effects such as nonlinear interaction with the ablated plasma plume. The scalable disk technology applied to high peak power lasers has resulted in today's most powerful ultraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Since their introduction as the world's first high average power industrial ultrafast lasers with 50 W of average power back in 2007 they have become the most successful commercial ultrafast lasers for direct micromachining [20]. The first high power industrial femtosecond lasers exceeding 100 W, demonstrated in 2013, were based on a CPA thin-disk regenerative amplifier, and obtained gigawatt peak powers [21]. Such peak powers are even possible in CPA-free systems using cm-size Pockels cells [22].…”
Section: Most Recent State Of the Artmentioning
confidence: 99%
“…Since their introduction as the world's first high average power industrial ultrafast lasers with 50 W of average power back in 2007 they have become the most successful commercial ultrafast lasers for direct micromachining [20]. The first high power industrial femtosecond lasers exceeding 100 W, demonstrated in 2013, were based on a CPA thin-disk regenerative amplifier, and obtained gigawatt peak powers [21]. Such peak powers are even possible in CPA-free systems using cm-size Pockels cells [22].…”
Section: Most Recent State Of the Artmentioning
confidence: 99%
“…Up to now, the highest average power RA systems are presented by thin-disk concept RAs. For example, up to 160 W average output power at 800 kHz PRF with 750 fs pulse duration were achieved in [4]. Up to 100 W average power at 400 kHz PRF with 800 fs pulse duration were reached in [5] employing Yb:YAG thin-disk active element.…”
Section: Introductionmentioning
confidence: 99%
“…An Yb:YAG TDL RA yielded as much as 160 W at 800 kHz, although with significantly longer 750 fs pulses [7].…”
mentioning
confidence: 99%